David Cronenberg's A History of Violence - Beaty, Bart (University of Toronto Press, 2017)
Arguably the most famous and critically acclaimed Canadian filmmaker, David Cronenberg is celebrated equally for his early genre films, like Scanners (1981) and The Fly (1986), and his dark artistic vision in films such as Dead Ringers (1988) and Crash (1996). The 2005 film A History of Violence was a mainstream success that marked Cronenberg's return to the commercial fold of Hollywood after years of independent art house filmmaking. His international reputation grew and the film was honoured with numerous awards and two Oscar nominations (for screenwriter Josh Olson and supporting actor William Hurt). David Cronenberg's A History of Violence - the lead title in the new Canadian Cinema series - presents readers with a lively study of some of the filmmaker's favourite themes: violence, concealment, transformation, sex, and guilt. Bart Beaty introduces us to Cronenberg's film, situating it in the context of its aesthetic influences, and argues for its uniquely English-Canadian qualities. The author contends that A History of Violence is a nuanced study of masquerade and disguise, a film that thwarts our expectations of film genre as much as it challenges our perception of national geography and cultural mythology. As a contribution to the Canadian Cinema series, the volume also presents readers with an overview of Cronenberg's career, the production history of the film, a discussion of its critical reception, and a filmography. David Cronenberg's A History of Violence is a book for fans, critics, and cinephiles alike